2017
DOI: 10.1002/cjg2.30075
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Methane Supply and Formation Process of Gas Hydrate Reservoir at Odp1247, Hydrate Ridge, Offshore Oregon

Abstract: The formation of gas hydrate reservoir in marine sediments is mainly controlled by methane supply and sedimentary burial. Based on the mass conservation of methane in gas hydrate system, a numerical model of gas hydrate formation was established considering the methane supplied by dissolved methane diffusion, pore water advection, and in situ methanogenesis. A case study of ODP site 1247 at the Hydrate Ridge, offshore Oregon shows that dissolved methane transported by molecular diffusion and pore water advecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, the rate of the already accumulated hydrate moving out of the base of HSZ also varies accordingly (Haacke et al, 2007;Karstens & Haflidason, 2018). Zheng et al (2017) presented a model for methane hydrate accumulation in marine sediment, which is capable of handling a transient sedimentation rate, and applied it to investigate the mechanisms of methane supply and hydrate accumulation in marine sediment at ODP Site 1247. The authors found that, although the multistage sedimentation rates at Site 1247 within a rather small range, the estimated hydrate saturation levels still deviate from that obtained if an averaged sedimentation rate was used.…”
Section: 1029/2019jb018851mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the rate of the already accumulated hydrate moving out of the base of HSZ also varies accordingly (Haacke et al, 2007;Karstens & Haflidason, 2018). Zheng et al (2017) presented a model for methane hydrate accumulation in marine sediment, which is capable of handling a transient sedimentation rate, and applied it to investigate the mechanisms of methane supply and hydrate accumulation in marine sediment at ODP Site 1247. The authors found that, although the multistage sedimentation rates at Site 1247 within a rather small range, the estimated hydrate saturation levels still deviate from that obtained if an averaged sedimentation rate was used.…”
Section: 1029/2019jb018851mentioning
confidence: 99%
“…Above the HSZ, the amount of dissolved methane is balanced by supply through advective and diffusive methane transport and consumption via micro organic oxidation and approaches zero when completely oxidized by microorganisms at the SMI (Borowski et al, 1996;Davie & Buffett, 2003a, 2003bBhatnagar et al, 2011;Zheng et al, 2017; Figure 3). Below the HSZ, methane hydrate is being carried out through the bottom of HSZ by the downward-moving sediment.…”
Section: Dynamic Equilibrium Considerationmentioning
confidence: 99%
See 2 more Smart Citations